1999
DOI: 10.1017/s1367943099000591
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive seasonality in the female scimitar-horned oryx (Oryx dammah)

Abstract: Faecal oestrogen and progestin analyses were used to assess ovarian activity in non-pregnant scimitar-horned oryx (Oryx dammah) during a 13-month interval. Mean (± SE) luteal phase, interluteal phase and oestrous cycle duration were 18.8 (± 0.5), 5.1 (± 0.2) and 23.8 (± 1.3) days, respectively. All females exhibited a synchronized anovulatory period that ranged from 36-95 days during spring. Short ovarian cycles (10.6 (± 0.8) days) were observed intermittently throughout the year and before the spontaneous res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The occurrence of recurring cyclic ovarian activity in cowseven while completely isolated from males-suggests that environmental cues are sufficient for annually up-regulating ovarian activity in wildebeest cows. This concurs with findings in other Bovidae (Sempere et al, 1996;Goodrowe et al, 1996;Thompson et al" 1998;Morrow et al, 1999;), but differs from the closest related species studied to date, the blesbok. Marais and Skinner (1993) found that female blesbok held in the presence of a male were polyestrous, whereas those in isolation remained anestrus until the introduction of a male.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The occurrence of recurring cyclic ovarian activity in cowseven while completely isolated from males-suggests that environmental cues are sufficient for annually up-regulating ovarian activity in wildebeest cows. This concurs with findings in other Bovidae (Sempere et al, 1996;Goodrowe et al, 1996;Thompson et al" 1998;Morrow et al, 1999;), but differs from the closest related species studied to date, the blesbok. Marais and Skinner (1993) found that female blesbok held in the presence of a male were polyestrous, whereas those in isolation remained anestrus until the introduction of a male.…”
Section: Discussionsupporting
confidence: 91%
“…Baseline values were determined by calculating the mean plus 1.5 standard deviations (Graham et al 1995;Morrow et al, 1999). Any value exceeding this criterion was considered elevated and removed from the set of nadir values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Morrow et al 1999;Wronski et al 2011) and springbok (Antidorcas marsupialis; Skinner et al 2001) reproduce year-round.…”
Section: Regional Variation In Reproductive Seasonality With Rainfallmentioning
confidence: 99%
“…Although germ cell production is less tightly coupled to hormonal variations in the male than in the female, non-invasive androgen monitoring in males has useful in characterizing seasonal patterns. Fecal and urinary steroid analysis has indicated seasonal influences on reproduction in females and/or males in several species, including the scimitar-horned oryx (Oryx dammah) (Morrow et al, 1999), the black-footed ferret (Mustela nigripes) (Brown, 1997), Maned wolves (Chrysocyon brachyurus) (Velloso et al, 1998), African wild dogs (Lycaon pictus) , Dalls sheep (Ovis dalli dalli) , Elds deer (Cervus eldi thamin) (Monfort et al, 1990) and Pere Davids deer (Elaphurus davidianus) . Once the relationship between steroid metabolite concentrations and reproductive events has been characterized for a species, non-invasive endocrine monitoring can be used as a tool to enhance the understanding and management of the species both in captivity and in the wild.…”
Section: Applicationsmentioning
confidence: 99%